Hoof Pathologies in Cattle - Kulynych, Serhii; Klymas, Anastasiia; Shabalin, Oleksandr; Zvenihorodska, Tamila; Petrenko, Maksym; Kolomak, Ihor; Tul, Oleksandra; Slynko, Viktor; Avramenko, Nataliia; Panasova, Tetiana; Omelchenko, Hanna (Journal of Multidisciplinary Applied Natural Science, 2026)
Hoof pathologies are among the most widespread orthopedic disorders in dairy cattle and are a major contributor to reduced animal welfare and productivity. The present study investigated the prevalence, clinical presentation, and treatment outcomes of the most common hoof lesions – digital dermatitis (Mortellaro’s disease), Rusterholz ulcers, purulent pododermatitis, and interdigital dermatitis – across multiple dairy farms in Ukraine. Clinical examinations and therapeutic procedures were performed on more than 9,800 cows from 7 farms during 2022–2023. Diagnosis was conducted during scheduled functional hoof trimming using an orthopedic crush and was confirmed based on lesion morphology, presence of exudate, odor, and pain response. A locally formulated topical powder composed of copper sulfate, zinc oxide, iodoform, and potassium permanganate was applied to purulent–necrotic lesions and compared with a control treatment using a commercial chemi-spray. Therapeutic efficacy was evaluated by lesion healing dynamics and locomotion scores (AHDB system) on days 3, 14, 21, and 45. Digital dermatitis was identified as the predominant lesion, accounting for 50–66% of all diagnosed hoof disorders. The locally formulated powder showed markedly superior therapeutic performance relative to the chemi-spray, accelerating tissue repair and improving locomotion, with full recovery achieved in 86.7–100% of treated cows, depending on farm and lesion type. These findings confirm the persistently high prevalence of hoof diseases in dairy herds and demonstrate the clinical advantage of an affordable, locally prepared treatment formulation. Routine functional trimming, early lesion detection, and evidence-based local therapy remain critical components of effective lameness management in modern dairy production systems.